Online tutoring system in college: Case study in private education - Mohd Arif, Rafidah; Khalifa, Othman Omran (2012)
Online tutoring system is one of the approaches used in today's private education which allows the tutors and students to communicate each other in a real time. However, some of the private colleges are still using the learning process in the classroom with a large number of students. Online tutoring system with objective to upgrade the conventional system to computer oriented learning to students of Diploma in Computer Science Multimedia (DCSM) at University College Shahputra (UCSA). This method makes the learning process more comfortable and efficient. System development life cycle (SDLC) combined with prototyping technique is used for the development process. The methodology is chosen because it attempts to reduce inherent project risk by breaking a project into smaller segments, provides easy to change during the development process and it is suitable used on developing online system. A survey had been done among lecturer of DCSM to identify the problems while the students learn in conventional way to find the better solution to the future's students. The complete system contain with a lot of tools for the convenience of students and lecturers. The major tools include the learning materials, bulletin and learning assessment such as quizzes and assignments. Students have been tested on using the system with taking the quiz while the lecturers been used the system on developing the set of learning materials. The system testing is focusing on acceptance testing to determine if the requirements of the specification system are met. The findings show that the online tutoring system is interesting and pleasant to be used. The students agree the online learning give them a flexibility on their learning compared to traditional learning. As the conclusion, students are satisfied with the content, structure and had a motivation on using online tutoring system.